Global Islamic Banking Efficiency: The Impact of Profitability, Liquidity, Solvency, and Technology - Alif Ahmad Sulthoni Putra Rofiqi; Guntur Kusuma Wardana (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2026)
This study aims to analyze the influence of profitability, liquidity, solvency, and technology on the efficiency of Islamic banks worldwide. This research is motivated by the importance of operational efficiency in enhancing the performance and competitiveness of Islamic banking amid global economic dynamics and the rapid development of digital technology. The variables used include profitability proxied by Return on Assets (ROA), liquidity by Financing to Deposit Ratio (FDR), solvency by Capital Adequacy Ratio (CAR), and technology (measured via IT cost proxy) as a supporting factor for bank operational efficiency. This study employs a quantitative approach using the Two-Stage Data Envelopment Analysis (DEA) method, with the first stage measuring the efficiency levels of Islamic banks and the second stage applying Tobit regression to analyze the influence of independent variables on efficiency. The data used are secondary data from global Islamic banks registered with the Islamic Financial Services Board (IFSB) for the period 2019–2024. The results indicate that profitability has a significant positive influence and liquidity has a significant negative influence, while solvency and technology show no significant influence on the efficiency of Islamic banks, thus requiring sound financial management and optimal utilization of technology to improve the performance and competitiveness of Islamic banking globally.